Hubungan Antara Sosial Budaya dengan Keberhasilan Pemberian ASI Eksklusif - Neta Alvira Nirmala; Danur Jaya; Ahmad Rizal (PPNI UNIMMAN, 2026)
Exclusive breastfeeding during the first six months of a baby's life is an important effort in improving children's health and growth and development. However, the success of exclusive breastfeeding still faces various challenges, one of which is influenced by socio-cultural factors that develop in society. The purpose of this study is to determine the relationship between socio-cultural factors and the success of exclusive breastfeeding at Grha Permata Ibu Hospital In 2025. This study used a quantitative method with an analytical observational cross-sectional design. The study population consisted of mothers with infants aged 6–9 months at Grha Permata Ibu Hospital. The sample size was 96 respondents, obtained using the Lemeshow formula with total sampling technique. Data collection was conducted using a sociocultural questionnaire and an exclusive breastfeeding success questionnaire. Data analysis was performed univariately and bivariately using the chi-square test. Based on the chi-square test results, a p-value of <0.001 was obtained, meaning that the p-value was <α (0.05), so it can be concluded that there is a relationship between sociocultural factors and the success of exclusive breastfeeding at Grha Permata Ibu Hospital in 2025.